Participation of Emerging Commercial Farmers in the Strategic Private-Sector Investment Interventions - Sandile Jason Mnikathi; Simphiwe Innocentia Hlatshwayo; Ojo Temitope; Mjabuliseni Simon Cloapas Ngidi (Agriculture)
Private sector investment interventions serve as essential mechanisms for creating efficient, cost-effective financial solutions and technological support for emerging farmers in developing economies, yet their successful implementation is influenced by various contextual and socioeconomic factors. Using a quantitative research approach, this study examined the factors influencing participation in private sector investment interventions among 121 emerging commercial farmers in KwaZulu-Natal, South Africa, utilizing a Poisson regression model to analyze four key intervention areas: credit access, market access, technical support, and spot supply. The first-hurdle model revealed that age and training skills negatively influenced market access while the training period showed positive influence, and similarly, the second-hurdle equation demonstrated that employment status and training period positively influenced participation intensity levels, though age maintained its negative impact. The findings of the first-hurdle model reveal that age and training skills negatively influenced market participation. The study concludes that employment status and training period positively impacted technical support adoption, with household size and training period emerging as significant determinants of intervention success. The private sector needs to develop strategic partnership models that encourage emerging farmers to participate intensively in interventions that are designed to improve their production and productivity. There is a need for targeted capacity-building programmes and enhanced extension services to improve emerging commercial farmers’ participation in private-sector initiatives.